2010
DOI: 10.1177/0886260510365864
|View full text |Cite
|
Sign up to set email alerts
|

Threats and Acts of Intimate Partner Violence Reported by Users at Norwegian Women’s Shelters

Abstract: Women (n = 87) at women's shelters in Norway, a country of high welfare and gender equality, reported a multitude of severe threats and actual acts of physical, sexual and psychological violence. An individual threatening to kill his partner represented a significant increased risk for experiencing serious acts of violence, especially when the threats were repeated. A self-administered questionnaire was sent to all the women's shelters. Experiences of violence were measured by The Severity of Violence against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…When a woman reports having experienced feelings of danger or having felt her life to be threatened, we must become alert because it is likely she will eventually be the target of violent behaviors. Our results clearly point in the same direction as Alasker et al (2011), who found threats of being killed posed an increased risk of experiencing serious acts of violence. Similarly, Campbell (2004) suggest women's risk of being murdered rises with the number of violent acts experienced, and women often underestimate the severity of the situation.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…When a woman reports having experienced feelings of danger or having felt her life to be threatened, we must become alert because it is likely she will eventually be the target of violent behaviors. Our results clearly point in the same direction as Alasker et al (2011), who found threats of being killed posed an increased risk of experiencing serious acts of violence. Similarly, Campbell (2004) suggest women's risk of being murdered rises with the number of violent acts experienced, and women often underestimate the severity of the situation.…”
Section: Discussionsupporting
confidence: 77%
“…In line with the study by Alasker et al (2011), our study captures the different abusive acts experienced by the women who came to a specialized care service for battered women and reveals being in a situation where a partner indulges in abuse suggesting a threat to life increases the relative risk of experiencing severe violence. As Straus et al (2009) suggest, perceived danger has important implications in considering IPV victims' perceptions of their situations relative to danger, not just the levels of abuse they are experiencing.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Reliability coefficients (Cronbach's α) ranged from 0.67 for symbolic violence to 0.72 for acts of ‘minor violence’ in our study and, for the six items in the sexual violence category, 0.81. More details about the categories and results of the physical violence experienced have been presented in a previous article (16). As the SVAWS does not have any questions about pregnancy and violence, we added one question: ‘Have you been exposed to violence directed at your abdomen when pregnant?’ and we used the four‐point scale.…”
Section: Methodsmentioning
confidence: 99%